An Overview of Islamic Law Against Buy and Sell Sand of Kebon with a Liberation System in Mount Wurung, Mojokerto Regency - Mochammad Nuril Misbach; Ryandono Muhammad Nafik Hadi; & Ari Prasetio (Center of Language and Cultural Studies, 2019)
The research is a field research where primary data were obtained from direct interviews using descriptive analysis techniques with inductive mindset. The research focused on an overview of the practice of buying and selling sand garden using slash system. Results show that the practice of buying and selling with the blow system are found in rural areas, one of them is in the Mount Wurung Mojokerto district, i.e. buying and selling blow sand garden. The price is based on the area of land to be cleared. For example, land with an area of 1400 m2, was agreed by both parties at a price of Rp. 40 million. No provision for the period of sand mining until mining is completed, it can reach 2 to 3 years. Both landowners and buyer do not know the content of sand in the soil of the kebon, which means to buy and sell the sand there is a potential gharar (lack of clarity on both sides) that allows each of them suffered a loss or gain. It is evident that sand trading kebon with the system is not in accordance with Islamic law because the seller or buyer cannot estimate the content and quality of sand in the plot. According to Madhab Hanafi Imam the sale and purchase that contained a little gharar and jizaf, and according to Madhab the Shafi'i Imam it was not permitted because there was potential gharar which allowed each of them has a loss or profit.